Detection of antibodies to anaplasma, bartonella and coxiella in rural inhabitants of the Caribbean area of Colombia - Salim Máttar (Revista MVZ Córdoba, 2006)
Objetive. To estimate the seroprevalence of antibodies to Anaplasma phagocytophilum (formerlyEhrlichia), Bartonella spp. and C. burnetii in Cordoba and Sucre departments, an important cattleraising and farming region of Colombia. Materials and methods. We analysed a representativecross-section of the population by collecting sera in 2003. All of the livestock farming individualsliving in towns within Cordoba and Sucre departments served as the base population from whichsamples were obtained, and all rural workers between 16 and 65 years of age were eligible toenrol. All sera were examined by IFA for the detection of IgG antibodies to Bartonella spp, Anaplasmaphagocytophilum and Coxiella burnetii. Results. esults. The overall seroprevalence of antibodies to one ormore of the studied agents was 56.8%. Of 81 serum specimens tested antibody to C. burnetii23.6%, were seropositive, 37.7% had antibody reactive with Bartonella and 20% of individualstested were seropositive to Anaplasma phagocytophilum. Conclusions. Our data indicate that theprevalence of antibodies to Bartonella, A. phagocytophilum and C. burnettii is high in our region.Our results suggest that infectious zoonotic diseases are very common among residents of theCaribbean area. This study demostratres for first time the presence of these microorganisms inColombia.